KEPEMILIKAN SERTA PEMBENTUKAN MODAL SOSIAL OLEH WISATAWAN DALAM MEMILIH HOUSE OF SAMPOERNA SEBAGAI DAYA TARIK WISATA - Asnurul Novia Narendra; Sri Kusuma Habsari; Deny Tri Ardianto (Universitas Merdeka Malang, 2019)
Everyone has social capital. Social capitals own by founding community of tourist locations and tourists. This study aims to prove the influence of social capital that is owned by each individual who then encourages them to choose House of Sampoerna as a tourism attraction and tourism place. Furthermore, this study also looks at how changes in social capital tourists have after visiting the House of Samporna. The study used the voices of 10 tourism of House of Samporna Surabaya. The results of the study answer the research objectives and find that social capital does not only function as a driver of preservation of tourist culture and tourist attraction by tourist founders, but also as a driver for people to decide on tourist destinations. In addition, through the social capital that is owned, the turism will get new relationships, new experiences, new knowledge, or the new work that the writer call as new social capital. That social capital is able to become additional social capital to sustain life in the future.